(untitled) (Rudarsko-geološko-naftni zbornik, 2019)
This paper proposes a method and a "tool" for assessment and management the risk of potable water supply in the amphibious military operation area through examples from military history. Amphibious landing is one of the most risky types of military operations, and the supply of military units with potable water in such operations represents a critical logistic function that may depend on the success or failure of a military operation. Potable water supply is a very important segment in the overall supply. Potable water is resources without soldier cannot endure long-term combat, for this are many examples in military history like is, for example, a battle of Hattin in 1187. The assessment and management of drinking water risk is an area of interest for military logistics and military geosciences. The water supply risk assessment matrix is a "tool" that can help military planners to realistically assess the risk, to determine the level of risk management and method how to control this risk.